Efectos cognitivos y conductuales secundarios al consumo de metanfetaminas. - Chaverra-Torres, Imara (2022)
Ecstasy or 3,4-methylenedioxmethamphetamine (MDMA), is a sympathomimetic drug for liver metabolism, popular with young people for its effects of euphoria, extroversion, increased sensory experiences, moderate derealization, empathy, and facilitation of interpersonal relationships. This article reviews in depth the topic of the acute, subacute and chronic cognitive and behavioral effects generated by the consumption of MDMA according to literature published between 2000-2020. Changes were described at the social level, both acute, as the reinforcement of prosocial behaviors, as chronic, as the decrease in empathic tasks and the appearance of aggressive behaviors. Regarding higher mental functions, a decrease in the processing and storage of information, alterations in operating, verbal and visual memory, poverty in verbal language and difficulty in decision-making associated with greater impulsivity were found in chronic consumers. In the affection, it was evidenced that people had symptoms associated with depression and anxiety, and an increased prevalence of psychotic episodes, both acutely and chronically. According to these findings, MDMA is a substance with harmful effects on the processing of tasks of social cognition, executive functions, mood modulation and perception of reality, with deterioration in the quality of life of the chronic consumer.